Borreria and Spermacoce species (Rubiaceae): A review of their ethnomedicinal properties, chemical constituents, and biological activities - Conserva, Lucia Maria; Júnior, Jesu Costa Ferreira (Pharmacognosy Reviews, 2012)
Borreira and Spermacoce are genera of Rubiaceae widespread in tropical and subtropical America, Africa, Asia, and Europe. Based on its fruits morphology they are considered by many authors to be distinct genera and most others, however, prefer to combine the two taxa under the generic name Spermacoce. Whereas the discussion is still unclear, in this work they were considered as synonyms. Some species of these genera play an important role in traditional medicine in Africa, Asia, Europe, and South America. Some of these uses include the treatment of malaria, diarrheal and other digestive problems, skin diseases, fever, hemorrhage, urinary and respiratory infections, headache, inflammation of eye, and gums. To date, more than 60 compounds have been reported from Borreria and Spermacoce species including alkaloids, iridoids, flavonoids, terpenoids, and other compounds. Studies have confirmed that extracts from Borreria and Spermacoce species as well as their isolated compounds possess diverse biological activities, including anti-inflammatory, antitumor, antimicrobial, larvicidal, antioxidant, gastrointestinal, anti-ulcer, and hepatoprotective, with alkaloids and iridoids as the major active principles. This paper briefly reviews the ethnomedicinal uses, phytochemistry, and biological activities of some isolated compounds and extracts of both genera.
Keywords: Alkaloids; borreria; flavonoids; iridoids; rubiaceae; spermacoce; terpenoids